Economic cycles and indicators of the labor market in the Northern Border of Mexico - Ramírez Rodríguez, Roberto (Posgrados de la División de Ciencias Económica Administrativas, 2023)
The objective that we have set ourselves in this paper is to carry out a measurement of the classic economic cycles in northern border estates of México, through a quarterly measurement that covers 1980-1 to 2020-4. Inspired by the tradition of measuring cycles of Burns and Mitchel (1946), as well as in the most recent contributions of Sherman (1991), the different economic phases of the economic cycle of labor market variables are identified, in particular the wage bill of IMSS workers and the inactive population available for work, contrasting it with the GDP of the border states on a quarterly basis. Most notable findings. He realizes the countercyclical behavior of discouraged or disillusioned workers, for some border states and for some contractive events. Of the same firm, a countercyclical behavior of the evolution of the wage bill was recorder in the context of the economic contraction of 2019-2020.